Virus detection and its association with symptoms during influenza‐like illness in a sample of healthy adults enrolled in a randomised controlled vaccine trial. Issue 3 (19th June 2012) - Howard, Peter F.; McCaw, James M.; Richmond, Peter C.; Nissen, Michael; Sloots, Theo; Lambert, Stephen B.; Lai, Michael; Greenberg, Michael; Nolan, Terry; McVernon, Jodie
<x xml:space="preserve">Abstract</x> Background Viral respiratory infections are associated with significant morbidity and mortality. Many new aetiological agents have been described recently. Objectives We looked for respiratory viruses in a population‐based sample of healthy adults with influenza‐like illness (ILI). We investigated host and spatio‐temporal associations with virus isolation and host, spatio‐temporal and virus associations with self‐reported symptoms. Patients/Methods We recruited 586 participants experiencing 651 illness episodes from a population of healthy adults enrolled in an influenza vaccine effectiveness trial. At ILI assessment visits, a respiratory swab was collected and tested for viruses using a combination of polymerase chain reaction (PCR) assays. Participants also completed a questionnaire detailing their clinical course in 336 episodes. Results Of 643 samples analysed, a virus was identified in 44%. Half were picornaviruses, with influenza and coronaviruses the next most common. Individuals with influenza were significantly less likely to have been immunised than the reference (virus negative) population (OR = 0·52 (0·31, 0·87) P = 0·01). The mean symptom score (95% CI) reported by individuals with influenza was significantly higher than in all other episodes [Influenza: 10·2 (9·4, 10·9); Other: 7·4 (7·2, 7·7); Difference (95% CI): 2·5 (1·5, 3·5); P < 0·001]. In an analysis restricted to influenza‐positive cases, the symptom score was not attenuated by vaccination. Conclusions Our findings indicate that a greater number of symptoms are displayed by individuals presenting with influenza confirmed ILI compared with other agents that cause ILI. While influenza vaccination reduced the probability of influenza virus detection, symptom score for influenza‐positive ILI was not attenuated.